2022
DOI: 10.1177/17534666221115054
|View full text |Cite
|
Sign up to set email alerts
|

Short-acting beta-2 agonist prescription patterns and clinical outcomes in Chinese patients with asthma: an observational study in mainland China for the SABINA programme

Abstract: Objectives: The SABINA CHINA study aimed to determine prescription data for asthma medication with a focus on SABA and ICS in a representative population of patients with asthma in China. Methods: SABINA China was a multicentre, observational, cross-sectional study with data collected retrospectively from a convenience sample of 25 tertiary centres across China. Patients (age ⩾ 12 years) with ⩾3 consultations/year were enrolled. Data were collected on clinical characteristics, asthma severity, and symptom cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Moreover, individuals who purchased their SABA with a prescription were more likely to have used preventer medication in the past seven days It appears a third of OTC SABA purchasers had less than normal healthy lung function. Prescription SABA use was associated with preventer use It is likely that this situation may have been worse in regional -rural areas where HCP shortages are more likely – this study was metropolitan area based [ 41 ] Bao et al China A multicenter, observational, cross-sectional study (SABINA III sub-analysis study) March and August 2020 Study targets: patients ≥ 12 years with a documented asthma diagnosis confirmed by the presence of recurrent symptoms and spirometry with, at least 3 annual consultations with HCP, and no other CRD other than asthma. Number of participants : 498 patients recruited from 25 tertiary centers (specialists) across China Used ⩾ 3 SABA canisters per year 5.2% were OTC SABA purchasers in the 12 months prior to the study visit 50% of participants purchased ⩾ 3 SABA canisters (12 months prior to the study visit) Not stated This study was to assess the treatment patterns and clinical outcomes in patients with predominantly moderate-to-severe asthma, who were managed at tertiary centers at China [ 36 ] Azzi et al Australia A real-world cross-sectional observational study October 2017 and October 2018 Study targets: SABA users who were aged 16 years or older, purchased over-the-counter SABA medication for themselves from community pharmacy, and were able to communicate in English.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, individuals who purchased their SABA with a prescription were more likely to have used preventer medication in the past seven days It appears a third of OTC SABA purchasers had less than normal healthy lung function. Prescription SABA use was associated with preventer use It is likely that this situation may have been worse in regional -rural areas where HCP shortages are more likely – this study was metropolitan area based [ 41 ] Bao et al China A multicenter, observational, cross-sectional study (SABINA III sub-analysis study) March and August 2020 Study targets: patients ≥ 12 years with a documented asthma diagnosis confirmed by the presence of recurrent symptoms and spirometry with, at least 3 annual consultations with HCP, and no other CRD other than asthma. Number of participants : 498 patients recruited from 25 tertiary centers (specialists) across China Used ⩾ 3 SABA canisters per year 5.2% were OTC SABA purchasers in the 12 months prior to the study visit 50% of participants purchased ⩾ 3 SABA canisters (12 months prior to the study visit) Not stated This study was to assess the treatment patterns and clinical outcomes in patients with predominantly moderate-to-severe asthma, who were managed at tertiary centers at China [ 36 ] Azzi et al Australia A real-world cross-sectional observational study October 2017 and October 2018 Study targets: SABA users who were aged 16 years or older, purchased over-the-counter SABA medication for themselves from community pharmacy, and were able to communicate in English.…”
Section: Resultsmentioning
confidence: 99%
“…Further, in the Australian context, it was evident that 70.1% to 73.9% of people with asthma participating in the studies who purchased SABA over-the-counter at community pharmacies were SABA over-users, meaning they used SABA more than twice a week in the past 4 weeks [ 15 , 36 ]. Our polled data for all studies reviewed indicate that 14% to 66.4% of asthma patients had purchased three or more SABA canisters over-the-counter over a period of 12 months [ 35 , 37 39 , 41 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a recent study in China reported that moderate-to-severe asthma was approximately 16% of newly diagnosed cases 4. Another cross-sectional study in 2020 found that 38.9% of Chinese patients did not achieve satisfactory asthma control 5…”
Section: Introductionmentioning
confidence: 99%
“…4 Another cross-sectional study in 2020 found that 38.9% of Chinese patients did not achieve satisfactory asthma control. 5 Previous studies have reported that nearly 90% of patients with severe asthma were cases of allergic asthma, 6 7 in which IgE plays a critical role. IgE leads to an inflammatory cascade by activating effector cells (eg, mast cells and basophils) through high-(FcεR I) or…”
Section: Introductionmentioning
confidence: 99%